FAKTOR-FAKTOR YANG MENGHAMBAT KINERJA PELAYANAN PUBLIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BATAM - riyanda, riko (Jurnal Niara, 2017)
Reforms will be able to meet the demands of the public, especially related to the improvement of the quality of public services, but it is still far from reality. Including services are provided by the Department of Population and Civil Registration Batam still not yet optimal. It is characterized by the many complaints from people who are not satisfied with the service that is given by the Department of Population and Civil Registration Batam.The approach used in this study is a qualitative approach. Type of research is descriptive.Methods of data collection is done by observation and documentation, informant selection technique is done by purposive sampling, data analysis performed by data reduction, data presentation and conclusion.The research found that investigators found the constraints of service in terms of Batam City Disdukcapil tangible, asurance and reability still not optimal. The cause is a factor of human resources and infrastructure, and systems that are not transparency. While the factors supporting online data base nationally integrated very helpful in order to avoid double data residence documents.